O processo de criação de ilustrações em mídias digitais - Steagall, Jaqueline (2008)
The present study is inserted in the current researches on visuality and its transformations with new technologies. As the mingling of art and the digital world is providing new ways for artistic possibilities, which in the research, was observed to be a complex network continuously being built, the reflection is on the illustration creation using digital software. This research was based on the theoretical approach by Charles Pierce, which deals with the phenomena occurring during the creation process. By analyzing some illustrations, this work shows how several languages (written, graphic and digital) are connected, resulting in digital, and how production in digital software involves different relationships between product and process. Its basics provide elements so that the construction of the work gains amplitude. This work theoretical foundation also received a contribution from Cecília Salles s ideas on the genesis of the work of art creative process, in which a sign relates to another one. Other authors are also approached, such as Arnheim, approaching the lines and forms that translate the artist s aims; Fayga Ostrower, with her reflections on the object form and their relations in the creative process; Kandisky, Klee and Bauhaus, in the employment of color; and Jonhson, in aspects referring to graphic interface, as well as the artist s communicative possibilities with the use of digital software. The analysis of works by some artists such as Lázaro Lúcio, Getúlio Pacheco Junior, Arthur Kenji and some by the author of this work showed the digital interferences in illustration creation. This work reflection focused on the creative process so that its elements can be understood in their complexity